Mechanical properties of PVC-based wood–plastic composites effected by temperature - Li, Jile; Huo, Ruili; Liu, Wenyi; Fang, Hai; Jiang, Lei; Zhou, Ding (Frontiers in Materials, 2022)
Compared with traditional wooden building materials, poly vinyl chloride (PVC) based wood plastic composites have advantages of good weather resistance, easy processing, energy saving and environmental protection, and have been popular and widely used in the field of civil construction and garden engineering in recent years. Due to the difference in thermal expansion coefficient between its component materials, the stress will accumulate in the Wood plastic composites (WPC) when the temperature changes, which will affect the mechanical properties of the material and structure. In order to explore the changes of mechanical properties of WPC under different temperatures and achieve the safe and controllable design, Differential Scanning Calorimetry (DSC) method was used in this paper to measure the glass-transition temperature of WPC between 78.45 ℃and 88.30 ℃, and the glass-transition temperature (Tg) was about 83.54 ℃. The tensile, compressive and bending mechanical properties tests of PVC based wood plastic composite materials under different temperatures were carried out in the ambient temperature chamber to obtain the failure characteristics, the load-displacement curve, and the influence of temperature on its mechanical properties.